Managing occupational stress among private Islamic school administrators and senior teachers in Klang Valley - Kayode, Bakare Kazeem (Institute of Education, International Islamic University Malaysia, 2010)
This study examines the causes and sources of occupational stress among Islamic school administrators and senior teachers. In addition, the study also investigates the Islamic technique or methods used by administrators and senior teachers to manage their stress at work. This study adopts a quantitative study using questionnaire adapted from Chyuan, (1998). Using a systematic sampling technique, a survey has been conducted on 130 samples from the population of 200. The Confirmatory factor analysis (CFA) findings reveals that—lack of support and resolving conflicts, workload, working conditions, administrators' responsibilities, and inadequate resources are the underlying factors of occupational stress among the respondents. The results also show that Solat oasis, Iman oasis, Imagination oasis, Meditation and Relaxation oasis and Remembrance oasis are the underlying dimensions of the common techniques used to manage or cope with occupational stress among the respondents. The implication of this study will alert the policy makers in educational institution (government and private) of the need to promote an awareness of health knowledge regarding administrators and senior teachers stress in the areas of administration, school climate and administrators' responsibilities through communication and training.